2014
DOI: 10.1179/1743284714y.0000000516
|View full text |Cite
|
Sign up to set email alerts
|

Application of low Ms temperature consumable to dissimilar welded joint

Abstract: The welding of dissimilar joints is very common in systems used in oil exploration and production in deep sea waters. Commonly involves welding of low carbon steel pipes with low alloy steel forgings both with inner Inconel clad. The forged steel part undergoes a process of buttering with Inconel or carbon steel electrode before the weld of the joint. The buttering process is followed by a process of residual stresses relief. The conventional way of reducing the level of residual stresses in welded joints is t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…Application of this mechanism has led to a number of martensitic welding alloys being developed. [3][4][5][6][7][8][9][10][11] The transformation of austenite to martensite (cRa9) is displacive and results in a shape deformation that is an invariant plane strain with a large shear component. 12 The magnitude of the shear, in conjunction with a dilatational strain, is sufficient to not only cancel the tensile stresses, but even create compression in the weld metal.…”
Section: Introductionmentioning
confidence: 99%
“…Application of this mechanism has led to a number of martensitic welding alloys being developed. [3][4][5][6][7][8][9][10][11] The transformation of austenite to martensite (cRa9) is displacive and results in a shape deformation that is an invariant plane strain with a large shear component. 12 The magnitude of the shear, in conjunction with a dilatational strain, is sufficient to not only cancel the tensile stresses, but even create compression in the weld metal.…”
Section: Introductionmentioning
confidence: 99%
“…The first of these solutions often leads to a loss of efficiency while the heat treatment is sometimes logistically very complicated. An alternative technique when dealing with welding of steels is to induce an adiffusional phase transformation during the cooling of the weld [3,4]. When austenite is transformed into martensite or bainite the phase transformation results in an invariant plane deformation and a normal plane expansion.…”
Section: The Welding Of Dissimilar Joints With Low Temperature Martensitic Transformation Filler Materialsmentioning
confidence: 99%
“…Because nickel acts as a FCC stabilizer through lowering the M s temperature, the 59 wt pct nickel content in Inconel 690 is sufficiently high to completely prevent strain-induced martensitic transformation. [19] It has been shown [20] that the yield strength and ultimate tensile strength of HIP'd Inconel 718 are independent of the material's oxygen content in the range of 25 to 850°C, and although the ductility is insensitive to oxygen content at room temperature, it decreases significantly with increasing oxygen content at elevated testing temperatures. However, to our knowledge no comparative study has hitherto been reported on the Charpy impact toughness fracture behavior between equivalently graded HIP'd and forged Inconel superalloy.…”
Section: Introductionmentioning
confidence: 99%